DeepGBM: A Deep Learning Framework Distilled by GBDT for Online Prediction Tasks - Ke, Guolin; Xu, Zhenhui; Zhang, Jia; Bian, Jiang; Liu, Tie-Yan (KDD '19 Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery & Data Mining, 2019)
Online prediction has become one of the most essential tasks in many real-world applications. Two main characteristics of typical online prediction tasks include tabular input space and online data generation. Specifically, tabular input space indicates the existence of both sparse categorical features and dense numerical ones, while online data generation implies continuous task-generated data with potentially dynamic distribution. Consequently, effective learning with tabular input space as well as fast adaption to online data generation become two vital challenges for obtaining the online prediction model. Although Gradient Boosting Decision Tree (GBDT) and Neural Network (NN) have been widely used in practice, either of them yields their own weaknesses. Particularly, GBDT can hardly be adapted to dynamic online data generation, and it tends to be ineffective when facing sparse categorical features; NN, on the other hand, is quite difficult to achieve satisfactory performance when facing dense numerical features. In this paper, we propose a new learning framework, DeepGBM, which integrates the advantages of the both NN and GBDT by using two corresponding NN components: (1) CatNN, focusing on handling sparse categorical features. (2) GBDT2NN, focusing on dense numerical features with distilled knowledge from GBDT. Powered by these two components, DeepGBM can leverage both categorical and numerical features while retaining the ability of efficient online update. Comprehensive experiments on a variety of publicly available datasets have demonstrated that DeepGBM can outperform other well-recognized baselines in various online prediction tasks.